Hubungan Regulasi Emosi dan Self Injuries Behavior Perempuan Dewasa Awal di Kota Bandung - Haura Atha Zhafira; Siti Qodariah (UNISBA Press, 2024)
Abstract. This study aims to determine the relationship between emotional regulation and self-injuries behavior in early adult women in Bandung City. This research includes quantitative research with correlational methods and using purposive sampling. The subjects of this study were 97 early adult women in Bandung, aged 18-25 years. The data analysis method uses spearman rank correlation. Data collection using inventory of statements about self-injury (ISAS) from Klonsky and Glenn (2009) for emotion regulation variables using emotion regulation questionnaire (ERQ) from Gross and John (2003). The results of data analysis showed a positive relationship between emotional regulation and self-injuries with a significance value of 0.018 < from alpha which is 0.5. This means that the lower the emotion regulation, the higher the level of self-injury behavior. Abstrak. Penelitian ini bertujuan untuk mengetahui hubungan regulasi emosi dan self-injuries behaviour pada perempuan dewasa awal di Kota Bandung. Penelitian ini termasuk penelitian kuantitatif dengan metode korelasional dan menggunakan purposive sampling. Subjek penelitian ini adalah perempuan dewasa awal di Kota Bandung berjumlah 97 orang, dengan usia 18-25 tahun. Metode analisis data menggunakan spearman rank correlation. Pengumpulan data menggunakan inventory of statements about self-injury (ISAS) dari Klonsky dan Glenn (2009) untuk variabel regulasi emosi menggunakan emotion regulation questionnaire (ERQ) dari Gross dan John (2003). Hasil analisis data menunjukan adanya hubungan positif antara regulasi emosi dan self-injuries dengan nilai signifikansi 0.018 < dari alpha yaitu 0.5. Artinya semakin rendah regulasi emosi, semakin tinggi tingkat self-injuries behaviour.